Coherent superpositions of three states for phosphorous donors in silicon prepared using THz radiation - S. Chick (Nature Portfolio, 2017)
Control of the interaction between atoms and their neighbours is important to quantum information processing and has been studied using two states. Here the authors demonstrate a more flexible control using a three-state superposition of donors in silicon using THz quantum beat spectroscopy.